Fruits in the Wilderness: A Potential of Local Food Resource - DESHMUKH, B. S.; VIDYA SHINDE (International Journal of Pharma and Bio Sciences, 2010)
The present study deals with the documentation and future potential of 29 wild edible fruit plants consumed by tribal communities from Kalsubai-Harishchandragad wild-life Sanctuary fall in Maharashtra state-India. Several plant species have been collected from the study areas which are of high economic food potential. Many plants reported are used in different formulation of ‘Ayurveda’ in Indian folk-medicine. They provide fibers which prevent constipation. Some examples are, Cordia dichotoma Frost.f.Prodr., Diospyros peregrina (Gaertn.)Gurke, Carrisa congesta Weight., Grewia abutilifolia Vent, Grewia villosa Willd, Rhus sinuata Thunb., Meyna laxiflora Robyns, Securinega leucopyrus (willd.)Muell., Elaeagnus conferta Roxb., Feronia elephuntum Corr., Cucumis setosus Cogn., Capparis zeylanica L. etc. Fruits of these species are edible and having nutritious food value which provides us the minerals like Sodium, Potassium, Iron, Calcium, Magnesium, phosphorus etc.